Facile exfoliation of natural talc into separated mesoporous magnesium silicate nano-sheets for effective sequestration of phosphate and nitrate ions: characterization and advanced modeling - Gaber, Walaa; Shehata, Nabila; El-Sherbeeny, Ahmed M.; Al Zoubi, Wail; Mehaney, Ahmed; Abukhadra, Mostafa R. (Frontiers in Chemistry, 2025)
Magnesium silicate nano-sheets were synthesized from natural talc by facile exfoliation and delamination methods as exfoliated product (EXTC) of 29.5 nm average pore diamter, enhanced surface area (103 m2/g), and adsorption perforamnces. The sucessful development of EXTC particles was followed based on different techniques and applied in effective sequestration of PO43- and NO3− ions from water. The EXTC product as adsorbent demonstrates remarkable effectiveness for both PO43- (257.9 mg/g) and NO3− (164.2 mg/g) as compared to several studied structures. Depending on the steric analysis of Monolayer equilibrium model, the interface of EXTC highly saturated with interactive receptors for the both ions but with higher abundant for PO43- (151.5 mg/g) as compared to NO3− (61.5 mg/g). This resulted in higher aggregation effect during the uptake of NO3− (4 ions per site) than PO43- (3 ions per site) which also donate the vertical orientation of these adsorbed ions and operation of multi-ionic sequestration mechanisms. The structure is highly recyclable and of significant safety and cane be applied in its spent or exhausted state as fertilizer. The energetic evaluation considering the Gaussian energy (<8.5 kJ/mol) as well as the sequestration energy (<4 kJ/mol), suggested the predominant impact of physical mechanisms (hydrogen bonds and electrostatic attraction), in addition to the impact of the weak chemical complexation. Furthermore, the thermodynamic functions declare the retention of these ions into the framework of EXTC by exothermic and spontaneous reactions.